2006
DOI: 10.1892/0891-6640(2006)20[1202:eoiaoo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenously Administrated Omeprazole on Gastric Juice pH and Gastric Ulcer Scores in Adult Horses

Abstract: The study was performed to evaluate the efficacy of omeprazole powder in sterile water, administered intravenously, on gastric juice pH in adult horses with naturally occurring gastric ulcers. Omeprazole (0.5 mg/kg, IV) was administered once daily for 5 days to 6 adult horses with gastric ulcers. Gastric juice was aspirated through the biopsy channel of an endoscope and pH was measured before and 1 hour after administration of omeprazole on day 1, and then before and after administration of omeprazole on day 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 23 publications
4
34
0
1
Order By: Relevance
“…This is consistent with some reports of minimal inter-individual variability in baseline gastric pH (Tellez et al, 2005;Andrews et al, 2006). Nevertheless, other studies have reported significant inter-horse variations (Daurio et al, 1999;JD Ruiz et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is consistent with some reports of minimal inter-individual variability in baseline gastric pH (Tellez et al, 2005;Andrews et al, 2006). Nevertheless, other studies have reported significant inter-horse variations (Daurio et al, 1999;JD Ruiz et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Other researchers found gastric pH increased above 4 during the first hour only in three out of six horses treated with 0.5 mg/Kg IV omeprazole (Andrews et al, 2006). In the present study, pH remained above 4 for up to 11 hours after injection of either 1 or 2 mg/Kg omeprazole; which is the minimum pH that should be maintained for as long as possible in order to improve the healing rate of gastric lesions (Armstrong, 2004).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Measuring intragastric pH has been widely accepted as a valid method for comparing and evaluating the efficacy of acid suppressants; however, the correlation between increased intragastric pH and outcome of acid‐related disorders has not been studied enough 1, 5, 6, 8, 9, 10, 11, 12. The aspiration of gastric juices, the placement of a pH electrode through a gastric fistula, and the placement of an pH catheter have been used as methods for measuring gastric pH 7, 8.…”
mentioning
confidence: 99%